Improving Precision in Small Area Proportion Estimation Using Logit Transformation: A Case of Internet Utilization in Papua’s Regencies, Indonesia (2021) - Sumarni , Cucu; Alifh , Muhammad; Sholihin , M. Rijalus; Putri , Christiana Anggraeni; Sohibien, Gama Putra Danu (Indonesian Scientific Journal, 2026)
The development of technology and communication reflects economic growth, with internet usage serving as one key indicator. While this indicator is generally available at the national or provincial level, reliable estimates at the regency level remain limited. Small Area Estimation (SAE) methods can address this gap by integrating survey data with census or administrative records. However, the basic SAE model may be less suitable for proportions, particularly in rare cases, due to violations of the normality assumption. This study shows that applying a logit transformation within the SAE framework improves the precision of proportion estimates. Using internet usage in Papua, Indonesia, as a case study, the results demonstrate that the logit-transformed SAE model outperforms both direct survey estimates and the basic SAE model.